2018
DOI: 10.3329/jsr.v10i1.32134
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Estimation of Cr and Pd in <I>Heteropneustes Fossilis</I> Fish due to Absorption from Tannery Waste Water

Abstract: The objective of this research is to reveal the pollution level and its impact on fresh water fish and finally, to estimate the concentration (ppm) of toxic metals chromium (Cr) (53.9 ppm) and lead (Pb) (13.2 ppm) in raw waste water (100%) and in fish (heteropneustes fossilis) (Cr 3.4 ppm, and Pb 2.0 ppm) by Atomic Absorption Spectrometry (AAS). Fresh tannery effluent is collected from Hazaribag-Dhaka and as early as possible some physicochemical parameters of that effluent such as Electrical Conductivity (EC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The Cd contamination in the aquatic environment exposed to fish also alters the oxidative stress biomarkers and induces aggressive behavior in the fish [28]. It was observed that fish exposed to highly polluted water containing toxic metals like Cr and lead has lower survival rates [29]. Chemicals like vanadate oligomers can also induce oxidative stress response in cardiac muscles of toad fish, Halobactrachus didactylus [30].…”
Section: Chemotoxicity Induced Oxidative Stress In Fishmentioning
confidence: 99%
“…The Cd contamination in the aquatic environment exposed to fish also alters the oxidative stress biomarkers and induces aggressive behavior in the fish [28]. It was observed that fish exposed to highly polluted water containing toxic metals like Cr and lead has lower survival rates [29]. Chemicals like vanadate oligomers can also induce oxidative stress response in cardiac muscles of toad fish, Halobactrachus didactylus [30].…”
Section: Chemotoxicity Induced Oxidative Stress In Fishmentioning
confidence: 99%
“…Most of the Schiff bases which are prepared from aryl‐amines with benzaldehydes, salicylaldehyde, amoxicillin, pyridoxal, and sulphamethoxazole, act as antibacterial agents . Schiff bases are able to coordinate with transition metals as electron donating atoms, via nitrogen lone pare electrons, and also the biological activities of the Schiff bases can be enhanced by these complexes, especially with Co, Ni, Cu, and Zn ions . In addition, Schiff base metal complexes are exhibiting suitable modes to stabilize them in various oxidation states .…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] Schiff bases are able to coordinate with transition metals as electron donating atoms, via nitrogen lone pare electrons, and also the biological activities of the Schiff bases can be enhanced by these complexes, especially with Co, Ni, Cu, and Zn ions. [14][15][16][17][18] In addition, Schiff base metal complexes are exhibiting suitable modes to stabilize them in various oxidation states. [19][20][21][22] They are applicable in medicinal and pharmaceutical fields due to a broad spectrum of biological and analytical activities like anti-inflammatory, analgesic, antimicrobial, anticonvulsant, antituberculosic, anticancer, antioxidant, anthelmintic, fungicidal, antidepressants, antitumor, nematocide, and anticarcinogenic.…”
mentioning
confidence: 99%